An evaluation of the impact of crystal symmetry on microwave dielectric properties of Sr1-2xNd2xTi1-xMgxO3 solid solution. Issue 15 (15th October 2019) - Ghobadi, Hosein; Lu, Wen-Zhong; Lei, Wen; Du, Kang; Wang, Fei
Abstract: Sr1-2x Nd2x Ti1-x Mgx O3 solid solutions for 0.05 ≤ x ≤ 0.30 were prepared and their microwave dielectric (MD) properties were evaluated. Refined crystal structures showed reduced symmetries as a function of x. The tolerance factor decreased steadily and non-linearly changed the τ f from +652.5 ( x = 0.10) to −28.95 ( x = 0.30). Raman spectra were collected to further support the less symmetrical crystal structures as well as the changes in MD properties. Oxidation state of Ti ions was investigated using XPS which presented high Ti 4+ /Ti 3+ ratios. A temperature dependent τ f was observed which could be because of the variations in oxygen vacancy. Finally, the optimal properties ε r  = 46.3, Q × f  = 13585 (GHz) and τ f  = +2.8 (ppm/˚С) were achieved in ceramics ( x = 0.265) sintered at 1425°С for 3 h.